Rules versus discretion in Post Keynesian fiscal policy - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2025)
During the neoliberal era, fiscal policy was side-lined: from a political economy perspective, it was seen as biased toward deficit and debt accumulation, while from a macroeconomic perspective, its potential role as a business cycle stabiliser was shifted to monetary policy, in line with the New Macroeconomic Consensus. This consensus codified the restrictive and passive orientation of fiscal policy through rules such as the European Stability and Growth Pact or Germany's 'Debt Brake.' Following a series of crises, fiscal rules have come under intense criticism, and Keynesian discretionary policy has regained popularity in both theory and practice. This article aims to provide a Post Keynesian perspective on fiscal policy: rejecting the idea of general equilibrium self-regulation and criticising the inherent limitations of (fiscal) policy, it advocates a functionally-oriented capital budgeting approach which favours an expansionary stance on the long-term budget balance and should not be left to the discretion of policy- makers. Instead, it should follow a transparent, non-overridable rule complemented in the short term by the unrestricted operation of automatic stabilisers and, only in exceptional cases, by discretionary measures to prevent severe depressions.
Keywords: E12; E62; H30; H60; H62; 330; Capital Budgeting; Functional Finance; Fiscal policy rule; Post Keynesianism